Strong Antimicrobial Activity of Silver Nanoparticles Obtained by the Green Synthesis in Viridibacillus sp. Extracts - Singh, Priyanka; Mijakovic, Ivan (Frontiers in Microbiology, 2022)
Recently, green silver nanoparticles (G-AgNPs) have gained much attention in medical science due to their extraordinary effects against multidrug-resistant microorganisms. The strong antimicrobial nature of G-AgNPs corresponds to their unique physicochemical properties such as size, shape, surface charge, and active surface groups available to interact with the pathogens. The current study demonstrates a simple, environmentally friendly, and economical method to produce G-AgNPs from an environmental isolate of Viridibacillus sp. The produced G-AgNPs were characterized by various analytical methods, including UV-vis spectroscopy, single-particle inductively coupled plasma-mass spectrometry (sp-ICP-MS), scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy (EDX), elemental mapping, transmission electron microscopy (TEM), dynamic light scattering (DLS), Fourier-transform infrared spectroscopy (FTIR), and Thermogravimetric analysis (TGA). The reduction of Ag+ to Ag◦ was observed by UV-vis spectroscopy, which demonstrated the formation of stable G-AgNPs with a Surface Plasmon Resonance (SPR) band at the maximum of 430 nm. TEM analysis demonstrated that the G-AgNPs are spherical with a 5-30 nm size range. The produced G-AgNPs were stable for more than one year in an aqueous solution at 4℃. Importantly, G-AgNPs showed remarkable antimicrobial activity against Gram-negative pathogens- E. coli and P. aeruginosa with MIC values of 0.1 and 4 μg/ml and MBC values of 1 and 8 μg/ml, respectively. This level of antimicrobial activity is superior to other AgNPs reported in the literature.